Do Tax Rates Encourage Entrepreneurial Activity? - Gordon, Roger (IMF Working Papers; Working Paper, 1997)
When the top personal tax rates are above the corporate rate, high-income individuals have an incentive to reclassify their earnings as corporate rather than personal income for tax purposes. U.S. tax law at least imposes strict limits on the extent to which employees in publicly traded corporations can engage in such income shifting. However, entrepreneurs setting up new firms can easily reclassify their income for tax purposes. This tax incentive therefore favors entrepreneurial activity. The paper discusses how best to subsidize entrepreneurial activity while avoiding other economic distortions.